2013
DOI: 10.1002/jgrd.50758
|View full text |Cite
|
Sign up to set email alerts
|

“Waveguidability” of idealized jets

Abstract: It is known that strong zonal jets can act as waveguides for Rossby waves. In this study we use the European Center for Medium‐Range Weather Forecasts (ECMWF) reanalysis data to analyze the connection between jets and zonal waves at timescales beyond 10 days. Moreover, a barotropic model is used to systematically study the ability of idealized jets to trap Rossby wave energy (“waveguidability”) as a function of jet strength, jet width, and jet location. In general, strongest waveguidability is found for narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 18 publications
(25 reference statements)
8
52
1
1
Order By: Relevance
“…In contrast to a single jet, a double jet regime associated with a profile for U is characterized by a confined sub-tropical jet with sharp edges wherein wind speeds change rapidly with latitude3. Such sharp sub-tropical jets are highly effective waveguides3031, a central requirement for QRA. Especially long-duration resonance events (as e.g.…”
mentioning
confidence: 99%
“…In contrast to a single jet, a double jet regime associated with a profile for U is characterized by a confined sub-tropical jet with sharp edges wherein wind speeds change rapidly with latitude3. Such sharp sub-tropical jets are highly effective waveguides3031, a central requirement for QRA. Especially long-duration resonance events (as e.g.…”
mentioning
confidence: 99%
“…The jet shift is in general the dominant robust response to Arctic warming and in fact seems apparent in many circulation indices shown by Francis and Vavrus [46] for example. Consequences for planetary wave behaviour will ultimately depend on the waveguiding ability of the jet as influenced by its position as well as its width and speed [59]. The projected future jet changes vary considerably, depending on the region and season, as a result of multiple influences in addition to the Arctic warming (e.g.…”
Section: Amplified Arctic Warming and Emerging Changes? Recent Researchmentioning
confidence: 99%
“…Manola et al [59] discussed the ability of idealised zonal jets to trap and guide Rossby waves. They found that this is most likely in narrow fast jets and that the Austral summer provides the most likely candidate for this.…”
Section: Waves and Resonancementioning
confidence: 99%
“…The anomalous upper level winds accompanying the change in convection constitute a Rossby wave source (Sardeshmukh et al 1987) and Rossby wave energy disperses away from the tropics, sometimes trapped by the atmospheric jets that can act as a Rossby wave guide (Branstator 2002). The strength of the waveguide response depends on the position of the Rossby wave source with respect to the jet and the width and strength of the jet itself (Manola et al 2013), such that in the winter season, the waveguide response is generally strongest.…”
Section: Remote Adjustments Through Atmospheric Rossby Wavesmentioning
confidence: 99%